2014
DOI: 10.1155/2014/317246
|View full text |Cite
|
Sign up to set email alerts
|

Vegan Triple-Ironman (Raw Vegetables/Fruits)

Abstract: Endurance sport requires a healthy and balanced diet. In this case report we present the findings of an ultra-triathlete (three times Ironman, means 11.4 km swim, 540 km bike, 125 km run in 41:18 h as a whole) living on a raw vegan diet and having finished the competitions under these nutritional conditions. To this end, the vegan ultra triathlete and a control group of 10 Ironman triathletes of similar age living on a mixed diet were investigated, using echocardiography and spiroergometry. In addition, blood … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 10 publications
1
21
0
1
Order By: Relevance
“…Additionally, recent case studies have also highlighted the capabilities of prominent vegan endurance athletes [115,116]. A case study by Wirnitzer and Kornexel (2017) reported energy intake and performance data for a female vegan cyclist competing in the 8-day Transalp Challenge 2004 (662 km, total altitude: 22,500 m).…”
Section: Exercise Performance and Plant-based Dietsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, recent case studies have also highlighted the capabilities of prominent vegan endurance athletes [115,116]. A case study by Wirnitzer and Kornexel (2017) reported energy intake and performance data for a female vegan cyclist competing in the 8-day Transalp Challenge 2004 (662 km, total altitude: 22,500 m).…”
Section: Exercise Performance and Plant-based Dietsmentioning
confidence: 99%
“…Left ventricular end diastolic diameter, end diastolic volume, and stroke volume also appeared higher in the vegan athlete. No dietary deficiencies or impaired health were indicated by bloodwork [116]. While such case reports are hardly sufficient for making recommendations about the adequacy of a vegetarian or vegan diet for endurance athletes, a large study (target n = 1500) is in progress comparing running performance among omnivore, vegetarian, and vegan runners, and results are forthcoming [117].…”
Section: Exercise Performance and Plant-based Dietsmentioning
confidence: 99%
“…Other studies have investigated plant‐based dietary patterns and endurance performance, but these have small sample sizes with cross‐sectional study designs (Hanne et al 1986; Nieman et al 1989; Nebl et al 2019) or are case studies (Leischik & Spelsberg 2014; Wirnitzer & Kornexl 2014). Deriving conclusions pertaining to the ability of a plant‐based diet to modulate endurance performance from these studies would be disingenuous as natural differences in physiology between groups could influence the results irrespective of diet.…”
Section: Specific Endurance Testing and Plant‐based Dietsmentioning
confidence: 99%
“…B. in Obst oder Fruchtsäften, und Getreideflocken oder Vollkornbackwaren, Zeitraum vegan ernährenden Athleten im Vergleich zu Omnivoren fehlen. Es existieren lediglich Studien mit Vegetariern und Mischköstlern oder von einzelnen, veganen Fallbeispielen, die keine Nachteile für die Leistungsfähigkeit aufzeigen (7, 10,14).…”
Section: Tipps Für Eisen Und Zinkunclassified